An overview of intellectual property within agricultural biotechnology in Brazil. Issue 1 (January 2019) - Figueiredo, L.H.M.; Vasconcellos, A.G.; Prado, G.S.; Grossi-de-Sa, M.F.
Abstract: Brazilian agricultural biotechnology has seen great advances in recent decades, especially in the development of GM crops, including soybean, cotton, and maize, which has placed Brazil in second place since 2013 in the ranking of countries with the greatest GM-cultivated area. However, patenting these technologies is somewhat more restrictive in Brazil than in other countries, such as the USA and Japan, especially concerning isolated biological material from nature. Hence, the intellectual protection of crops in Brazil is encompassed by sui generis rights and/or the patenting of only the development process. Given the current scenario and the importance of biotechnology for the Brazilian agriculture sector, it is necessary to deeply study the patent system for recently developed technologies to identify opportunities for enterprises and national institutes to act in this area. The application of novel biotechnological strategies to agriculture will contribute to the expanding agriculture sector and become part of the solution to global challenges. Through this study, we can identify the major companies developing and protecting their agrobiotechnologies. Additionally, a more detailed analysis verifies that although there are some restrictions in Brazilian laws, GM patent applicants find ways to obtain intellectual protection for the tools they use in the development of GM crops, which include regulatory sequences, gene constructs and production methodologies. Mechanisms to stimulate investment in Brazilian research companies and public policies must be consolidated, allowing investment and public–private partnerships in this sector, with the aim of applying biotechnological knowledge and turn it into products demanded by society.